Cognitive functions measured with a battery of CNS VS tests and the subjective assessment of memory, concentration impairment and reduction in the quality of life in women after menopause - Bojar, Iwona; Witczak, Mariusz; Stępniak, Anna; Łyszcz, Robert; Raczkiewicz, Dorota; Humeniuk, Ewa (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : The aim of this work was to learn about the relations between potential cognitive dysfunctions in women after menopause and the subjective feeling of memory impairment, attention disturbance and reduction in the quality of life. The research examined cognitive functions with CNS VS tests and the subjective feelings of reduction in the quality of life, memory impairment and attention disturbance after menopause. Material and methods : The studied group consisted of women from south-eastern Poland, with a minimum of 2 years after their last period. The criteria which allowed them to take part in the research were: age 50-65, a general good health condition, at least elementary education and FSH ≥ 30 mlU/ml. During the qualification stage for the research, a short MoCA test was performed in order to include in the study only patients with no traits of dementia. The assessment of cognitive functions was performed using a diagnostic apparatus CNS – VitalSigns (Polish version). The reduction in the quality of life, memory and concentration impairment were studied by using a questionnaire specially prepared for this research; answers to all questions were in a four-degree scale: never have any symptoms, mild, average, severe signs. Study results have been statistically analyzed. Results : Subjective assessment of increasing memory and concentration impairment and reduction in the quality of life were significantly connected with the standard of cognitive functions obtained by using CNS VS tests. The worse self-assessment of the memory, the lower the test results achieved by women in the area of memory, visual memory and psychomotor speed (p < 0.05). As to the subjective opinions on concentration impairment, a similar pattern was found in the area of the Neurocognitive Index (NCI), memory, visual memory, executive functions, psychomotor speed, focusing and cognitive adaptability (p < 0.05). On the other hand, the subjective opinion on the reduction in the quality of life after menopause, was relevantly connected with four cognition domains: NCI, speed of processing, executive functions and cognitive adoptability (p < 0.05). Conclusions : Postmenopausal women are vulnerable to adverse changes in the mental sphere and hence specific preventative actions should be taken in this group.